2020
DOI: 10.1111/acem.13898
|View full text |Cite
|
Sign up to set email alerts
|

Ibuprofen Plus Acetaminophen Versus Ibuprofen Alone for Acute Low Back Pain: An Emergency Department–based Randomized Study

Abstract: Objectives Patients with low back pain (LBP) are often treated with nonsteroidal anti‐inflammatory drugs (NSAIDs). NSAIDs are modestly effective for LBP, but many patients with LBP continue to suffer despite treatment with these medications. We compared pain and functional outcomes 1 week after emergency department (ED) discharge among patients randomized to a 1‐week course of ibuprofen plus acetaminophen versus ibuprofen plus placebo. Methods This was a randomized, double‐blind study conducted in two urban ED… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 17 publications
0
26
0
Order By: Relevance
“…Although method reproducibility and inferential reproducibility have now been addressed for the PACE trial, results reproducibility (also called replication) has not [8,10,11]. However, a recent study by Friedman et al compared the combination of the NSAID ibuprofen and paracetamol with the combination of ibuprofen and placebo for patients with acute LBP reporting to two American emergency departments [36]. Although the research question, setting, patient population, and follow-up time were different from the PACE trial, the conclusions regarding the efficacy of paracetamol were the same as those made in the original PACE study.…”
Section: Discussionmentioning
confidence: 99%
“…Although method reproducibility and inferential reproducibility have now been addressed for the PACE trial, results reproducibility (also called replication) has not [8,10,11]. However, a recent study by Friedman et al compared the combination of the NSAID ibuprofen and paracetamol with the combination of ibuprofen and placebo for patients with acute LBP reporting to two American emergency departments [36]. Although the research question, setting, patient population, and follow-up time were different from the PACE trial, the conclusions regarding the efficacy of paracetamol were the same as those made in the original PACE study.…”
Section: Discussionmentioning
confidence: 99%
“…This was most convincingly demonstrated in a series of trials by Friedman et al examining patients presenting to the emergency department with low back pain. 31 , 32 , 34 , 33 The SPACE trial also showed that an opioid strategy was not more effective than a nonopioid strategy in patients with chronic low back pain (or moderate to severe pain from knee or hip osteoarthritis), while it was also more likely to cause adverse events. 58 …”
Section: Many Patients With Low Back Pain Are Still Receiving the mentioning
confidence: 99%
“…The studies by Nadler, and Williams were included in the Cochrane review [23][24][25]. The study by Friedman was published afterward [27]. Table 1 illustrates the overall limited evidence available comparing paracetamol versus placebo.…”
Section: Article Highlightsmentioning
confidence: 99%
“…The two remaining trials show that there is no difference in effect of paracetamol versus placebo. This holds true for paracetamol taken regularly, as needed and as addition to Ibuprofen [24,27]. For chronic low back pain, there was only one trial, but the publication of this study has been retracted [26], thus for chronic low back there is no good evidence for or against the efficacy of paracetamol available.…”
Section: Article Highlightsmentioning
confidence: 99%